Aibika/Bele, Abelmoschus manihot (L.) Medik. - Proeston, S.R.; International Plant Genetic Resources Institute (1998)
Cultivated extensively in the lowlands of Melanesia, aibika is one of the highest yielding leafy vegetables, and is nutritious and easy to grow. This monograph reviews its taxonomy, origin, uses, genetic resources, ecology, agronomy, reproductive biology, crop protection, breeding and research needs. Appendices listing a basic descriptor list, details of the Papua New Guinea collection, insects found aibika in Pacific Island countries and research contacts are included. (Abstract © CAB ABSTRACTS, CAB International)